Kinematic and electromyographic analysis of the Nordic Hamstring Exercise - Ditroilo, M.; de Vito, G.; Delahunt, E. (Journal of Electromyography and Kinesiology, 2013)
The Nordic Hamstring Exercise (NHE) has been introduced as a training tool to improve the efficiency of eccentric hamstring muscle contraction. The aim of this study was to perform a biomechanical analysis of the NHE. Eighteen participants (20.4 ± 1.9 years) performed two sets of five repetitions each of the NHE and maximal eccentric voluntary contraction (MEVC) of the knee flexors on an isokinetic dynamometer whilst knee angular displacement and electrical activity (EMG) of biceps femoris were measured. EMG was on average higher during the NHE (134.3% of the MEVC). During the forward fall of the NHE, the angle at which a sharp increase in downward velocity occurred varied between 47.9 and 80.5 deg, while the peak knee angular velocity (pVelocity) varied between 47.7 and 132.8 deg s-1. A significant negative correlation was found between pVelocity and peak EMG (r = -0.62, p < 0.01) and EMG at 45 deg (r = -0.75, p < 0.01) expressed as a percentage of peak MEVC EMG. Some of the variables analyzed exhibited good to excellent levels of intra- and inter-session reliability. This type of analysis could be used to indirectly monitor the level of eccentric strength of the hamstring muscles while performing the NHE and potentially any training- or injury-related changes.